2017
DOI: 10.5455/ajvs.263048
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Broiler Growth Performance, Physiological and Fear Responses Using Three Monochromatic LED lights

Abstract: Key words:Behavior, Broilers, Fear Response, Monochromatic LED Light, Performance.The present study aimed to investigate the effect of rearing avian broiler under different monochromatic LED light color on their growth performance, physiological and fear responses. One hundred and thirty five unsexed day-old avian 48 chicks were randomly allocated into three light treatment (n=45 bird) each treatment 3 replicates (n=15 bird). The treatments were white, green, and blue light. The obtained results demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 19 publications
9
28
0
4
Order By: Relevance
“…Olanrewaju et al (2016) suggested that the modern commercial poultry facilities should be using dim light to optimize feed conversion and reduce energy utilization. Mohamed et al (2017) indicated that the lowest FCR was observed in birds exposed to light produced from LED light than those of the other treatments. In contrast, Mendes et al (2013) found that the FC and FCR for broilers reared under different light sources remain unaffected.…”
Section: Feed Consumption and Feed Conversion Ratiomentioning
confidence: 87%
See 2 more Smart Citations
“…Olanrewaju et al (2016) suggested that the modern commercial poultry facilities should be using dim light to optimize feed conversion and reduce energy utilization. Mohamed et al (2017) indicated that the lowest FCR was observed in birds exposed to light produced from LED light than those of the other treatments. In contrast, Mendes et al (2013) found that the FC and FCR for broilers reared under different light sources remain unaffected.…”
Section: Feed Consumption and Feed Conversion Ratiomentioning
confidence: 87%
“…Similar results, were obtained by Hossein and Zaghari (2016) who found that the body weight, were highest at the birds reared under warmwhite light emitted from LED lamps compared to the incandescent treatment. Also, Olanrewaju et al (2016) and Mohamed et al (2017) reported that the overall growth and production parameters of BW and BWG which examined in birds exposed to light produced from incandescent bulb group were statistically lower than those of the birds subjected to light emitted from the blue, green, and Cool-LED bulb. Contradictory, BW and BWG were not exhibit statistically differences due to light sources (Ahmed et al, 2015;Cao et al, 2008;Kristensen et al, 2006).…”
Section: Body Weight and Body Weight Gainmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is confirmed with Senaratna et al (2016) indicated that blue or green light is preferable to red or white light for broiler because it keeps the birds calmer and is chosen by the birds themselves. Also, Mohamed et al (2017) demonstrated that broiler reared under blue and green light had higher body weight and weight gain compared with white light. In addition, Balabel et al 2017showed that it is strongly recommended to use an alternative cycling between green and blue light colors in broiler farms to get high growth performance.…”
Section: -Growth Performance 1-1-live Body Weight (Lbw) and Body Weimentioning
confidence: 97%
“…Erkek piliçleri farklı renklerde LED ampuller ile büyüten Ke et al (2011), mavi ışığın beyaz, kırmızı ve yeşil ışıklara göre canlı ağırlık ve göğüs eti ağırlığını arttırdığını, et kalitesini iyileştirdiğini (pH, su tutma kapasitesi ve protein içeriği yükselmiş, pişirme kaybı ve yağ içeriği azalmış), süperoksit dismutaz ve glutatyon peroksidaz enzimlerinin aktiviteleri ile toplam antioksidan kapasitesiyi arttırdığını ve lipid peroksidasyonunu azalttığını belirlemişlerdir. Etlik piliçlere günün 23 saati beyaz, mavi ve yeşil renk aydınlatma uygulayan Mohamed et al (2017) ise mavi ve yeşil LED ampul kullanılan gruplarda canlı ağırlık, canlı ağırlık artışı ve yem tüketiminin arttığını, yemden yararlanmanın iyileştiğini, korku/stresin azaldığını ve refahın olumlu etkilendiğini saptamışlardır. Bunların yanı sıra, erkek etlik piliçlerde mavi ve yeşil LED ampuller ile aydınlatmanın bağışıklık sistemini olumlu etkilediği (Xie et al, 2008;Zhang et al, 2014) ve ayrıca mavi ışığın stresi azalttığı (Xie et al, 2008) bildirilmiştir.…”
Section: Introductionunclassified